Association of Central Corneal Thickness among Myopic and Emmetropic Patients Visiting Ophthalmology Department of a Tertiary Care Hospital in Islamabad. - Sufian Ali Khan; Muthair Shah; Ahad Sharif; Saif Ullah; Anjum Imdad; Ayesha Khalid (Journal of Rawalpindi Medical College, 2023)
Aim The aim of the study was to determine difference between central corneal thickness (CCT) among myopic and emmetropic eyes.